The savings and growth nexus in Bangladesh - Rahman, Sultan Hafeez; Pabon, Md. Nahid Ferdous (BRAC Institute of Governance and Development (BIGD), 2022)
The paper investigates the causal relationship between Bangladesh’s gross domestic savings (GDS) and gross domestic product (GDP). Using yearly time series data from 1980 to 2018, we employ two short-run and one long-run causality tests to identify the direction of causality between these two variables. We find unidirectional causality running from growth to savings in the short run. However, long-run causality is not found in any direction under any of the tests.